Relationship between the growth of euryale ferox salisb. And some limnological parameters - Alfasane, Md Almujaddade; Khondker, Moniruzzaman; Begum, ZN Tahmida (Dhaka University Journal of Biological Sciences, 2011)
Euryale ferox was grown in meso-scale culture by using mature fresh fruits. Seeds kept dry for a few days were found completely non-viable. A two year ex situ study on the growth and the associated limnological parameters of E. ferox showed some distinct relationship. Among these petiole length of E. ferox positively correlated with photosynthetic active radiation (PAR), day length, rainfall, humidity, air temperature, water temperature, pH, total dissolved solids (TDS), conductivity, nitrate-nitrogen (NO3-N) and soluble reactive phosphorus (SRP). Among these parameters positive correlation between petiole length and rainfall was found to be significant at 1% level. Leaf area of E. ferox showed positive correlation with PAR, day length, rainfall, humidity, air temperature, water temperature, pH, TDS, conductivity, NO3-N, SRP and planktonic phaeopigment concentrations. Among these parameters positive correlation between leaf area and day length was found to be significant at 5% level. However, both leaf area and petiole length of E. ferox showed negative correlation with alkalinity, DO, soluble reactive silicate (SRS) and chlorophyll a. Key words: Euryale ferox; Growth; Limnological parameters DOI: http://dx.doi.org/10.3329/dujbs.v19i1.8942 DUJBS 2010; 19(1): 41-46